Allotype analysis to determine the origin of cytomegalovirus immunoglobulin‐G after allogeneic stem cell transplantation. Issue 6 (4th November 2014) - Yamazaki, R.; Tanaka, Y.; Nakasone, H.; Sato, M.; Terasako‐Saito, K.; Sakamoto, K.; Akahoshi, Y.; Nakano, H.; Ugai, T.; Yamasaki, R.; Wada, H.; Ishihara, Y.; et al.
Abstract Background Cytomegalovirus (CMV) reactivation still remains a major problem following allogeneic hematopoietic stem cell transplantation (HSCT). Patients and methods In this study, we analyzed an immunoglobulin allotype, IgG1m(f), in CMV‐seropositive HSCT recipients and their donors to distinguish donor‐derived antibody from recipient‐derived antibody. Eight donor‐recipient pairs were informative regarding the appearance of donor‐derived immunoglobulin‐G (IgG), as the recipients were homozygous null for the IgG1m(f) allotype and the donors were IgG1m(f) positive. In these patients, total IgG, IgM, and allotype‐specific IgG against CMV were measured by enzyme‐linked immunosorbent assay. All subjects were monitored for at least 9 months after HSCT with (n = 5) or without (n = 3) CMV reactivation. Results Donor‐derived CMV IgG tended to be elevated earlier in patients with CMV‐seropositive donors than in those with CMV‐seronegative donors. In 1 patient with a CMV‐negative donor, donor‐derived CMV IgG was not detected until late CMV reactivation. In 3 patients without CMV reactivation, donor‐derived CMV IgG was also elevated within 1–6 months after HSCT. Conclusion In conclusion, the CMV serostatus of the donor may be related to the timing of the appearance of donor‐derived CMV IgG and the reconstitution of humoral immunity against CMV, regardless of the CMV antigenemia level after HSCT.